2020
DOI: 10.1111/hel.12741
|View full text |Cite
|
Sign up to set email alerts
|

Review: Extragastric diseases andHelicobacter pylori

Abstract: The involvement of Helicobacter pylori infection in many extra‐gastroduodenal manifestations remains a fascinating field of investigation. However, for several of these supposed associations, the potential pathogenic mechanism remains unclear. The present review highlights the main associations of H pylori with extra‐gastroduodenal manifestations reported during the last year. We searched for the most relevant studies on this topic, published between April 2019 and March 2020, identified using the term “Helico… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 95 publications
0
47
0
3
Order By: Relevance
“…Among the H. pylori infection-derived extra-gastric manifestations, the link with energy management, weight gain and metabolic homeostasis is still up for debate (6).…”
Section: H Pylori Infection and Metabolic Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the H. pylori infection-derived extra-gastric manifestations, the link with energy management, weight gain and metabolic homeostasis is still up for debate (6).…”
Section: H Pylori Infection and Metabolic Diseasesmentioning
confidence: 99%
“…diabetes, obesity, metabolic syndrome) and autoimmune and inflammatory (e.g. autoimmune gastritis, immune thrombocytopenia purpura, autoimmune thyroid diseases, inflammatory bowel diseases) disorders (6).…”
Section: Introductionmentioning
confidence: 99%
“…A global systematic review concluded that approximately 4.4 billion individuals are positive for H. pylori infection worldwide, and its prevalence varies from 18.9 to 87.7% of the populations [ 2 ]. This infection is also associated with an increased incidence of extra-gastric diseases, such as cardiovascular, respiratory, hepatic, and allergic diseases [ 3 ]. Successful eradication of H. pylori infection would effectively reduce the prevalence of the mentioned complications, especially gastric cancer, and is therefore considered as one of the controllable factors in the process of gastric carcinogenesis [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gastric MALT lymphoma is a low-grade NHL, and is known to be a consequence of chronic inflammatory processes induced by H. pylori [ 9 , 19 ]. Intensive research in recent years using modern molecular techniques along with cellular and animal models has demonstrated the importance of H. pylori as a carcinogen and has greatly expanded the knowledge of the interaction of these spiral bacteria on the lymphoproliferative processes [ 20 , 21 , 22 ]. The pathogenesis of H. pylori -dependent chronic gastritis leading to metaplasia and activation of the carcinogenic processes is still the subject of intense research.…”
Section: Role Of Bacteria In Gastrointestinal Lymphomamentioning
confidence: 99%